Thermal impact of replacing constant voltage by low-frequency sine wave voltage in RF ablation computer modeling. (October 2020) - Pérez, Juan J.; González-Suárez, Ana; Nadal, Enrique; Berjano, Enrique
Highlights: This study assesses the impact of replacing DC voltage by low-frequency AC voltage in RF ablation computer modeling. Replacing DC voltage by low-frequency AC voltage does not appear to have an impact on the lesion size. Replacing DC voltage by low-frequency AC voltage provokes thermal oscillations at the tissue near the ablation electrode. Abstract: Background and objectives: A constant voltage (DC voltage) is usually used in radiofrequency ablation (RFA) computer models to mimic the radiofrequency voltage. However, in some cases a low frequency sine wave voltage (AC voltage) may be used instead. Our objective was to assess the thermal impact of replacing DC voltage by low-frequency AC voltage in RFA computer modeling. Methods: A 2D model was used consisting of an ablation electrode placed perpendicular to the tissue fragment. The Finite Element method was used to solve a coupled electric-thermal problem. Quasi-static electrical approximation was implemented in two ways (both with equivalent electrical power): (1) by a constant voltage of 25 V in the ablation electrode (DC voltage), and (2) applying a sine waveform with peak amplitude of 25√2 V (AC voltage). The frequency of the sine signal ( f AC ) varied from 0.5 Hz to 50 Hz. Results: Sine wave thermal oscillations (at twice the f AC frequency) were observed in the case of AC voltage, in addition to the temperature obtained by DC voltage. The amplitude of the oscillations: (1) increased with temperature, remaining more or less constant after 30 s; (2) was of up to ±3 °C for very low f AC values (0.5 Hz); and (3) was reduced at higher f AC values and with distance from the electrode (almost negligible for distances > 5 mm). The evolution of maximum lesion depth and width were almost identical with both DC and AC. Conclusions: Although reducing fAC reduces the computation time, thermal oscillations appear at points near the electrode, which suggests that a minimum value of f AC should be used. Replacing DC voltage by low-frequency AC voltage does not appear to have an impact on the lesion depth.